Legal Pluralism and Maqāṣid Al-Sharīʿah in Regulating Cooperative Finance under Indonesia’s Financial Services Authority - Defilania, Oktri; Gunadi, Ariawan; Rohaya, Nizla; Khutub, Muhammad (Sharia and Law Faculty of Sunan Kalijaga Islamic State University Yogyakarta, 2025)
Abstract: The transfer of regulatory authority over financial-service cooperatives to the Financial Services Authority (OJK) through the Financial Sector Development and Strengthening Law (Law No. 4/2023, PPSK Law) represents a paradigm shift in Indonesia’s legal landscape. Cooperatives, historically governed under a separate regime and supervised by the Ministry of Cooperatives and SMEs, are now incorporated into the national financial regulatory system. This article examines the conceptual implications of the reform through a normative juridical method supported by statutory, conceptual, and comparative approaches. Primary legal sources include the PPSK Law, Cooperative Law, Financial Services Authority Law, and OJK Regulation No. 47/2024, while secondary sources comprise scholarly literature, expert opinions, and prior research. The analysis employs three conceptual frameworks: consumer protection theory, Maqāṣid al-Sharīʿah in Islamic economic law, and legal pluralism. Findings show that OJK supervision enhances legal certainty, protects members’ financial assets, and aligns cooperative consumer rights with those of bank customers, thereby advancing the Maqāṣid principles of protection of wealth (ḥifẓ al-mā), justice (‘adālah), and balance (tawāzun). Nevertheless, the reform raises concerns about potential erosion of cooperative autonomy and the risk of marginalizing small-scale or community-based cooperatives. These tensions highlight the need for proportional and collaborative regulatory design that accommodates cooperative values while ensuring accountability and stability. The discussion concludes that cooperative supervision under OJK can serve as both a safeguard and a challenge: it strengthens governance but may undermine cooperative identity if implemented rigidly. Future empirical research is recommended to assess the real impact of the reform across regions and cooperative models. Abstrak: Peralihan kewenangan pengawasan koperasi jasa keuangan kepada Otoritas Jasa Keuangan (OJK) melalui Undang-Undang Pengembangan dan Penguatan Sektor Keuangan (UU No. 4 Tahun 2023, UU PPSK) merepresentasikan perubahan paradigma dalam lanskap hukum Indonesia. Koperasi, yang secara historis diatur dalam rezim terpisah dan diawasi oleh Kementerian Koperasi dan UKM, kini masuk dalam sistem regulasi keuangan nasional. Artikel ini mengkaji implikasi konseptual dari reformasi tersebut melalui metode yuridis normatif dengan pendekatan perundang-undangan, konseptual, dan komparatif. Sumber hukum primer mencakup UU PPSK, UU Perkoperasian, UU Otoritas Jasa Keuangan, serta Peraturan OJK No. 47 Tahun 2024, sedangkan sumber sekunder meliputi literatur akademik, pendapat ahli, dan hasil penelitian terdahulu. Analisis dilakukan dengan menggunakan tiga kerangka konseptual: teori perlindungan konsumen, Maqāṣid Asy-Syarīʿah dalam hukum ekonomi Islam, dan pluralisme hukum. Hasil penelitian menunjukkan bahwa pengawasan OJK meningkatkan kepastian hukum, melindungi aset keuangan anggota, serta menyelaraskan hak-hak konsumen koperasi dengan nasabah bank, sehingga memperkuat prinsip maqāṣid berupa ḥifẓ al-māl (perlindungan harta), ʿadālah (keadilan), dan tawāzun (keseimbangan). Namun demikian, reformasi ini juga menimbulkan kekhawatiran terkait potensi terkikisnya otonomi koperasi dan risiko marginalisasi terhadap koperasi kecil berbasis komunitas. Ketegangan ini menegaskan perlunya desain regulasi yang proporsional dan kolaboratif, yang mengakomodasi nilai-nilai koperasi sekaligus menjamin akuntabilitas dan stabilitas. Kajian pada artikel ini menyimpulkan bahwa pengawasan koperasi oleh OJK dapat berfungsi ganda: sebagai instrumen penguatan tata kelola, tetapi juga berpotensi melemahkan identitas koperasi jika diterapkan secara kaku. Penelitian empiris lebih lanjut sangat disarankan untuk menilai dampak nyata reformasi ini di berbagai daerah dan model koperasi.